Reproducing the Stylized Facts that Motivate Models of International Trade with Heterogeneous Firms Using the World Bank Enterprise Surveys - Alejandro Ria\~no (Center for Economic Studies and ifo Institute (CESifo), 2023)
This article shows how to use the publicy-available firm-level surveys produced by the World Bank Enterprise Surveys (WBES) to reproduce the stylized facts that characterize firm heterogeneity and its relationship with global engagement, as established by Bernard et al. (2007) for manufacturing firms in the U.S. The article describes how to incorporate this exercise in different teaching activities such as small group classes and homework and courseworks assignments. The activities proposed allow students to develop skills handling and analyzing firm-level data and, since WBES surveys are available for more than 150 countries since 2002, they offer an unique opportunity to evaluate the extent to which the stylized facts established from U.S. data are also representative of countries of different size and stage of development. The activities proposed connect the theory of trade with heterogeneous firms to the real-world empirical evidence that motivated the development of these models.
Keywords: A22; F12; 330; teaching international trade; heterogeneous firms; exports; imports; economic data; stylized facts